Binding of Polyethylene Glycol Imidazolium Hydrogen Sulfate to Magnetic Nanoparticles and Its Application as a Novel Recyclable Solid Acid Catalyst in the Friedländer Synthesis of Quinolines under Solvent-Free Conditions. (21st April 2022) - Fallah-Mehrjardi, Mehdi; Karimi, Ali Mohammad; Banitaba, Sayed Hossein
Abstract: For the first time, a new acidic imidazolium-based ionic liquid supported on magnetic nanoparticles (MNP@PEG-ImHSO4 ) was synthesized and characterized by Fourier transform infrared spectroscopy (FT-IR), field-emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), energy-dispersive X-ray (EDAX), thermogravimetric analysis (TGA), and X-ray diffraction (XRD) techniques. Afterwards, its catalytic activity was investigated in the Friedländer synthesis of quinolines through a condensation reaction between 2-aminoaryl ketones and α -methylene ketones under solvent-free conditions. The catalyst could readily be separated from the reaction mixture using an external magnet and could be reused in subsequent reactions with no significant loss of activity. Graphical Abstract: